2008
DOI: 10.1007/s00436-008-0999-z
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean visceral leishmaniasis associated with acute lymphoblastic leukemia (ALL)

Abstract: We report a case of Mediterranean visceral leishmaniasis (MVL) associated with acute lymphoblastic leukemia (ALL) from the South of Iran. The patient, a 12-year-old girl, was known to be a case of ALL and had bone pain and prolonged fever on referral. A trephine biopsy revealed a hypocellular marrow with many amastigotes. Moreover, by specific polymerase chain reaction (PCR) on peripheral blood, a 145 bp band corresponding to kDNA from the genus Leishmania was detected and the species was identified as Leishma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…Ascaris lumbricoides can cause obstruction and abdominal masses that can be confused with tumors. The fever, leukopenia, anemia, thrombocytopenia, hepatosplenomegaly and lymphadenopathy of visceral leishmaniasis [79] can mask a malignancy. Treatment for presumed parasitemia may thereby delay malignancy diagnosis.…”
Section: Parasitic Infectionsmentioning
confidence: 99%
“…Ascaris lumbricoides can cause obstruction and abdominal masses that can be confused with tumors. The fever, leukopenia, anemia, thrombocytopenia, hepatosplenomegaly and lymphadenopathy of visceral leishmaniasis [79] can mask a malignancy. Treatment for presumed parasitemia may thereby delay malignancy diagnosis.…”
Section: Parasitic Infectionsmentioning
confidence: 99%
“…Domingues et al [2009] described a 15-year-old Brazilian boy with Hodgkin´s Disease in his second remission when biopsy of an enlarged lymph node showed both Leishmania amastigotes and pathologic findings consistent with Hodgkin’s disease. Fakhar et al [2008] reported on a 12 year-old girl in Iran with acute lymphocytic leukemia and biopsy-confirmed VL. VL has also been described during treatment for solid tumors, including head and neck and colon cancers [Kopterides et al, 2007].…”
Section: Visceral Leishmaniasis and Malignancymentioning
confidence: 99%
“…It is rare in infants. Though, there are case reports of Leishmaniasis, malaria and other vector borne diseases seen in association with leukemias, filariasis co-existing with ALL has not been documented (Fakhar et al 2008). To the best of our knowledge, this is the first case report of ALL with filariasis in an infant.…”
Section: Discussionmentioning
confidence: 85%